Smart Home Sleep Respiratory Monitoring System Based on a Breath-Responsive Covalent Organic Framework - Yan, Mengwen; Hao, Qing; Diao, Shanyan; Zhou, Fan; Yichen, Chen; Jiang, Nan; Zhao, Chao; Ren, Xiao-Rui; Yu, Fuchao; Tong, Jiayi; Wang, Dong; Liu, Hong (ACS nano, 2024)
A smart home sleep respiratory monitoring system based on a breath-responsive covalent organic framework (COF) was developed and utilized to monitor the sleep respiratory behavior of real sleep apnea patients in this work. The capacitance of the interdigital electrode chip coated with COFTPDA‑TFPy exhibits thousands-level reversible responses to breath humidity gases, with subsecond response time and robustness against environmental humidity. A miniaturized printed circuit board, an open-face-mask-based respiratory sensor, and a smartphone app were constructed for the wearable wireless smart home sleep respiratory monitoring system. Leveraging the sensitive and rapid reversible response of COFs, the COF-based respiratory monitoring system can effectively record normal breath, rapid breath, and breath apnea, enabling over a thousand cycles of hour-level continuous monitoring during daily wear. Next, we took the groundbreaking step of advancing the humidity sensor to the clinical trial stage. In clinical experiments on real sleep apnea patients, the COF-based respiratory monitoring system successfully recorded hour-level sleep respiratory data and differentiated the breathing behavior characteristics and severity of sleep apnea patients and subjects with normal sleep function and primary snoring patients. This work successfully advanced humidity sensors into clinical research for real patients and demonstrated the enormous application potential of COF materials in clinical diagnosis.